ANALISIS KONDISI TATA AIR UNTUK PEMANTAUAN KEKRITISAN DAERAH ALIRAN SUNGAI JANGKOK - Humairo Saidah; Lilik Hanifah (Jurnal Tanah dan Sumberdaya Lahan, 2020)
An assessment of Jangkok River’s water system conditions is needed to its monitoring watershed criticality to prevent various problems and for conservation purposes. The aim of this research was to assess the condition of Jangkok River’s water system over the past 17 years using the Republic of Indonesia Minister of Forestry Regulation No. 61/Menhut-II/2014 concerning Monitoring and Evaluation of Watershed Management. The assessment results showed that Jangkok is in a good conditions but it tends to deteriorate that was indicated by the tends of increasing Flow Regime Coefficient and Annual Flow Coefficient. The mean of Flow Regime Coefficient’s value of upstream is 65.66 (medium) and downstream is 333.63 (very high), while the increasing rate of 7.72 and 59.13 a year respectively. The mean Annual Flow Coefficient is 0.14 for upstream and downstream 0.22, which increases 0.99% and 0.93% a year respectively. The tendency of the value of the Water Use Index decreased with an annual average of 0.31 and a rate of decline of 0.005 a year. The assessment result shows that Jangkok is GOOD in water system condition but it requires more attention to maintain its function and ensure water sustainability.